Instrument model to evaluate children-friendly school program at elementary school in Indonesia - Siti Maisaroh; Samsul Hadi; Dedek Andrian (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study aims to develop an instrument to evaluate Indonesia’s children-friendly school program (CFSP). This development research is then used to evaluate CFSP in Indonesia. Instrument development using the context, input, process, product (CIPP) approach and outcome evaluation. The population of this study was all students in the provinces of Riau and Yogyakarta. The research sample is of the students taken randomly from 108 schools that run CFSP. Data analysis used content validity, construct analysis, construct reliability, and descriptive statistics to evaluate the current CFSP. The content validity result shows that only 50 can be used of 56 of the developed items. The construct validity analysis result shows that all indicators obtained from theoretical exploration are valid and reliable. The model fit test shows that the instruments and data obtained from the respondents fit statistically. The results of the evaluation analysis show that the CFSP has been running well, but three indicators are still at a poor level and need to be improved so that the CFSP can run optimally. Indicators needing improvement are the completeness of documents and indicators of student participation, parental participation, community institutions, and the business world. This instrument became the new product to evaluate completely CFSP program because this instrument evaluates not only the process or implementation program but also every process until the program's outcome. Recommendations that need to be considered by stakeholders are to improve CFSP performance so that CFSP can maximally develop student character.